Physical contradictions ruling out photonic quantum nonlocality - Vatarescu, Andre (Annals of Mathematics and Physics, 2022)
A series of physical contradictions can be identified in an opinion article published in December 2015 (A. Aspect, “Closing the Door on Einstein and Bohr’s Quantum Debate,” Physics 8, 123, 2015) claiming definitive proof of quantum nonlocality based on entangled pairs of photons. For example, experimental results published simultaneously in Physical Review Letters (250401 and 250402, 2015) were theoretically fitted with distributions containing a dominant unentangled component, contradicting the need for maximally entangled states underpinning quantum nonlocality. Such contradictions were ignored by the 2022 Nobel Prize Committee raising doubts about the validity of their decision.